Linguistics why it matters - Pullum, Geoffrey K. (Polity, 2018)
"Linguistics applies the analytical methods of the sciences to a subject formerly thought to belong mainly to the humanities: language. Geoff Pullum offers a stimulating introduction to the many ways in which the study of linguistics matters. With its close relationships to other disciplines, the subject has a compelling human story to tell"--Provided by publisher.